Plasma Lipid and Lipoprotein Concentrations in Pregnancy Induced Hypertension - Syeda Rabia Bukhari, Alia Firdus, Sadaf Jalal, Lamia Yusuf, Surraya Israr, Amanullah Bhutto, (Pakistan Journal of Medical & Health Sciences, 2023)
Background and aim: Variation in serum lipid profile is associated with hypertension. Abnormal lipid profile directly affects the endothelial dysfunction and significantly associated with atherosclerotic cardiovascular diseases. Hypertension is the pregnancy toxaemia associated key feature which is considered to be caused by vasospastic phenomena in placenta, kidney, brain, and uterus. The current study aimed to assess plasma lipid and lipoprotein concentrations in pregnant women with hypertension (PIH). Methods: This study was conducted on 66 (36 PIH cases, 30 control cases) age matched women in the Department of Obstetrics and Gynecology, Moulvi Ameer Shah Memorial Hospital, Peshawar from October 2021 to June 2022. The criteria for preeclampsia were proteinuria, and proteinuria after pregnancy, hypertension, edema, and reversal of hypertension. Subjects' fasting venous blood samples were collected. Plasma was isolated from heparine anticoagulated blood. In a preservative bottle (500 mg/1000 mL urine) of Na2B4O7, urine was collected after 24 hours. Urine and plasma were kept at -80°C until the assay. Total cholesterol levels, HDL-C, and triglyceride were enzymatically measured. The amount of spectrophotometric and malondialdehyde was measured for plasma lipid peroxidation. SPSS version 26 was used for data analysis. Results: There was a significant increase in proteinuria, mean diastolic, and systolic pressure of preeclampsia patients than the control group. Total triglyceride, malondialdehyde (MDA), low density lipoprotein cholesterol (LDL-C), and apolipoprotein B (apo-B) in a study group were significantly higher as compared to control. Whereas the study group had lower high density lipoprotein cholesterol (HDL-C) than that of control group. The total cholesterol concentration, plasma protein, gestational age, apo-A, and hemoglobin had no statistical significance in both groups. Conclusion: The present study suggested that abnormal lipid metabolism, high triglycerides, specifically LDL-C and lipid peroxides, and low HDL-C concentrations, may lead to the vascular dysfunction and preeclampsia is associated with oxidative stress. There are only minor differences in lipoprotein concentrations and serum lipid between PIH women and women with uncomplicated pregnancy. Keywords: Plasma lipid, Lipoprotein concentration, Pregnancy-induced hypertension